(untitled) (Rome, 2006)
Food security is an issue of global concern, and it will be determined to a large extent by developments in plant nutrition. This publication examines key topics relating to plant nutrition with special reference to integrated nutrient management for crop production, including present and future demand for plant nutrients, soil fertility and crop production, management of plant nutrients and their sources, nutrient management guidelines for major field crops, economic and policy issues, food quality and consumer health, and environmental issues.
Keywords: Plants,Food; Nutrition,Quality